An analysis on the accuracy of the yield curve in predicting the Malaysian economy: A 20 years' perspective - Rahman, Maya Puspa (2017)
Previous researchers have argued that yield curve contains information for future growth, and to a certain extent, was accurate in predicting recessions through the signal of yield curve inversion. This paper provides new evidence on the long- and short-run relationship between economic growth and yield spread in Malaysia, based on a 20-year span of data ranging from January 1996 to December 2016. By using the autoregressive distributed lag (ARDL) framework, the sample data is divided into three samples after taking into consideration the two major crisis occurred in Malaysia over the last two decades. We find strong evidence of cointegration between the yield spread and growth, concurring on the long-run and short-run dynamics between them. Though significant, the instability of the yield spread to affect the movement of growth does not support the priori expectation on the predictive ability of the yield curve in Malaysia.